Legal Protection of Children's Human Rights as Students in Online Learning During the Covid-19 Pandemic - Rachma, Ayu Widya; Husodo, Jadmiko Anom (International Journal of Sustainability in Research, 2024)
The legal protection of children's human rights in the education sector in Indonesia must be the government's main concern. The law provides for the rights children must receive, including the right to education. This is because during the COVID-19 pandemic, governments have found it difficult to provide educational legal protections to children. This article uses normative legal research to examine the legal protection of children's right to education during the COVID-19 pandemic and the role of states in realizing children's right to education.